2011
DOI: 10.2527/jas.2010-3377
|View full text |Cite
|
Sign up to set email alerts
|

COMPANION ANIMALS SYMPOSIUM: Microbes and gastrointestinal health of dogs and cats1

Abstract: Recent molecular studies have revealed complex bacterial, fungal, archaeal, and viral communities in the gastrointestinal tract of dogs and cats. More than 10 bacterial phyla have been identified, with Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria, and Actinobacteria constituting more than 99% of all gut microbiota. Microbes act as a defending barrier against invading pathogens, aid in digestion, provide nutritional support for enterocytes, and play a crucial role in the development of the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 74 publications
2
104
1
8
Order By: Relevance
“…Opposed results were obtained with neomycin which is also an aminoglycoside as gentamicin and erythromycin which are considered the most effective [8]. Holle et al [19] in their investigation reported that erythromycin increases intestinal motility and therefore reduces bacteria because normal intestinal motility is a major defense mechanism against the attachment of pathogenic bacteria in the small intestine [1]. In the current research in intestinal dysbiosis occurred, owing to that, Klebsiella spp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Opposed results were obtained with neomycin which is also an aminoglycoside as gentamicin and erythromycin which are considered the most effective [8]. Holle et al [19] in their investigation reported that erythromycin increases intestinal motility and therefore reduces bacteria because normal intestinal motility is a major defense mechanism against the attachment of pathogenic bacteria in the small intestine [1]. In the current research in intestinal dysbiosis occurred, owing to that, Klebsiella spp.…”
Section: Resultsmentioning
confidence: 96%
“…They serve as a defending barrier against invading pathogens, aid in digestion and energy collection from the diet, assist in nutritional entrance into enterocytes and stimulate the local immune system [1]. Gastrointestinal surgery procedures due to its anatomical and physiological attributes is demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal diseases are commonly diagnosed in all kinds of domestic and farm animals, including exotic pet mammals [2], dogs [3,4], cats [4,5], or horses [6], among others. Many of them are idiopathic, chronic, relapsing disorders of the gastrointestinal tract, such as the inflammatory bowel diseases (IBD) [7].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is supported by recent studies that have revealed a genetic susceptibility to defective bacterial clearance in Boxer dogs with GC. Differential expression of pathogen recognition receptors were identified in dogs with enteropathies (Suchodolski 2011). In boxer dogs with large bowel diarrhea the macrophages in the lamina propria and submucosa, as well as these aggregates in regional lymph nodes showed immunoreactivity with polyclonal E. coli antibody.…”
mentioning
confidence: 98%